2011
DOI: 10.1111/j.1533-2500.2011.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Opioid Prescribing Practices and Associations with Repeat Opioid Prescriptions in a Contemporary Outpatient HIV Clinic

Abstract: Objectives Among persons in current HIV outpatient care, data on opioid prescribing are lacking. This study aims to evaluate predictors of repeat opioid prescribing and to characterize outpatient opioid prescribing practices. Methods Retrospective cross-sectional study of persons ≥ 18 years in HIV outpatient care who completed an annual behavioral assessment between June 2008 and June 2009. Persons were grouped by ≤ 1 and ≥ 2 opioid prescriptions (no-repeat-opioid and repeat-opioids, respectively). Independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…These data are consistent with a prior study, which found that only 57 % of HIV-infected patients initiating opioid treatment had a documented indication for opioids. 7 Our finding that HIV-infected patients were more likely to receive any and high-dose opioids, and less likely to receive long-term opioids are unlikely to be explained by differences in pain-related diagnoses alone. In fact, recent data from our group found that HIV-infected patients were less likely to report moderate or severe pain than uninfected patients (34 % vs. 49 %, p<0.05).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…These data are consistent with a prior study, which found that only 57 % of HIV-infected patients initiating opioid treatment had a documented indication for opioids. 7 Our finding that HIV-infected patients were more likely to receive any and high-dose opioids, and less likely to receive long-term opioids are unlikely to be explained by differences in pain-related diagnoses alone. In fact, recent data from our group found that HIV-infected patients were less likely to report moderate or severe pain than uninfected patients (34 % vs. 49 %, p<0.05).…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with previous literature, patients receiving opioids had a greater prevalence of HCV, major depression, alcohol and drug use disorders and pain-related diagnoses. 4,7,12,[38][39][40][41] Unique to our cohort, we demonstrated that these conditions were more common among HIV-infected patients who were prescribed opioids in comparison to their age/sex/race/ ethnicity/site-matched controls. Generally, non-schedule II short-acting medications were the most common types of opioids received.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations